PENGEMBANGAN MEDIA VIDEO BERBASIS KEARIFAN LOKAL KEDIRI UNTUK MENCERMATI KARAKTER TOKOH-TOKOH YANG TERDAPAT PADA TEKS FIKSI SISWA KELAS IV SEKOLAH DASAR - Puri Putri Maharani; Alfi Laila; Novi Nitya Santi (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2020)
This study aims to describe: (1) need assessment of students and teachers for the development of video media based on local wisdom, (2) validity of media experts from material experts. This research is a type of research development (Research and Development). The research development model refers to the ADDIE procedure with 5 stages: (a) Analysis; (b) Design; (c) Development; (d) Implementation; (e) Evaluation. Data collection methods by observation, interview, questionnaire and documentation. Evaluation of the validity of instructional media involved five material and media expert lecturers. The results of this research show that; 1) teachers and students alike need the development of video media; 2) video media based on local wisdom based on the results of the validation of material experts obtained a score of 97.85 included in the very good category and media design experts obtained an average value of 97.14 which means that the developed media was included in the very good category, and 3) based on the results of small-scale trials the result is 73% classified in the feasible category and further on the large-scale trial yields 87% data, so it is declared feasible to be used in SDN Sukorame 2.